Rebecca Adams’ Model of "Loving Mimesis": An Overview and Assessment - Taylor, Matthew (Anthropoetics, 2020)
Though René Girard’s mimetic theory focuses on rivalry, conflict and scapegoating, there has long been an interest in “positive mimesis.” Girard’s comments on “good mimesis” were scattered and ambivalent, making it difficult for Girard scholars to define it concretely. Rebecca Adams proposed a very striking model of positive mimesis, “loving mimesis,” that shows how it might operate in the context of “internal mediation.” Adams redraws the mimetic triangle using the intriguing example of the coquette, Girard’s classic “pseudo-narcissist.” Adams suggests an alternative process through which this mimetic relation becomes a truly “intersubjective” one, meaning that no “objectification” takes place. Unfortunately, her explication is divided between a somewhat opaque formal exposition, and a supplementary personal vignette which is lucid but largely unknown. Adams’ scholarship was also interrupted, leaving her model undeveloped. I revisit and explicate Adams’ model of positive mimesis by grafting her separate accounts together. First, I review Adams’ personal vignette, then I review her formal exposition. I also assess what I see as the strengths and shortcomings of each as I proceed. In the leadup to her formal model, Adams undertakes an ambitious “deconstruction” of Girard’s system, making valid and insightful points. However, her own results could arguably be deconstructed in the same way. The dynamic model of loving mimesis is by far the most intriguing and innovative component of Adams’ project, but it needs more concrete examples and much more elaboration. Nevertheless, Adam’s model may be the most promising of the attempts to understand positive mimesis.